The Role of Learning Strategies and Their Implications for the Effectiveness of Deep Learning - Asih Andriyati Mardliyah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to examine the role of learning strategies in supporting the implementation of the deep learning approach to enhance learning effectiveness in Indonesia. This research employs a literature review method by analyzing various articles related to learning strategies and the application of the deep learning approach in education. The findings indicate that learning strategies significantly contribute to fostering learning motivation, material comprehension, and the achievement of learning objectives. The appropriate selection of learning strategies can also help students develop critical thinking, creativity, and independence. Furthermore, the implementation of the deep learning approach has proven effective in improving conceptual understanding, critical thinking skills, problem-solving abilities, active student engagement in learning, and the personalization of learning materials. However, the successful implementation of this approach requires teacher readiness, adaptation to local contexts, and adequate support from the educational system and digital literacy. Therefore, integrating appropriate learning strategies with the deep learning approach is a strategic step toward realizing quality education and sustainably improving student learning outcomes.